Biotechnology 3 - Hawkhill Associates Inc. (Madion, WI : Hawkhill Assoc., 2002)
Genetic Engineering explores the brave new world of cloning, gene splicing, in-vitro fertilization, BGH and more. Features interviews with biologists, activists and environmentalists. Gene Guns focuses on a new technology to transfer genes from one plant or animal into another
Title from title screen
Keywords: Biotechnology